Innovation and creativity in batik motif design: a study of students’ art theses - Guntur Guntur; Ponimin Ponimin; Muhammad Arif Jati Purnomo (Creativity Studies, 2023)
This article discusses the process and products of innovation in batik motif design in the Fashion Design study program of the Faculty of Art and Design in Indonesian Institute of the Arts, Surakarta, Indonesia. The research population is 15 students and the report descriptions of each of their art theses. In the context of the innovation process, it was found that artefacts, ceremonies, legends, nature, and performing art phenomena all served as sources of inspiration for innovation in the design of batik motifs which were manifested in various alternative sketches, developed to become selected sketches, and perfected in the final design. In the context of the products of innovation, it was found that the innovations in batik motif design were based on single and multiple motifs that were arranged based on repetition, single, additive, and hypotactic patterns on the medium of a large piece of cloth, using techniques of drawing, dabbing, and painting, to become a piece of batik cloth or a batik painting.